REVIEW OF THE IMPLEMENTATION OF FOREIGN REPORTING APPLICATIONS (APOA) IN IMMIGRATION SUPERVISION AT THE CLASS I IMMIGRATION OFFICE OF TPI BENGKULU - Agwildo Futra Purwanto (Polteknik Imigrasi, 2019)
Bengkulu Province is the prayer center of tourism for foreign tourists. Various tourist objects in the area attract foreign tourists to visit so that the growth of the accommodation business also increases. The increased growth of the accommodation business needs to be integrated with the Foreigner reporting application. This writing aims to analyze the application policy of reporting foreigners at the immigration office using literature and field observation methods. The results of the writing show that the Foreigner Reporting Application provides convenience in carrying out foreigner surveillance activities in the working area of ​​the TPI Bengkulu Class I Immigration Office.